The Power of Transportation that Perpetuates Structural Poverty : A Study of Pedicab Drivers at Bratang Terminal, Surabaya - Faris Dwi Febrianto; Dania Afro Humairo; Pambudi Handoyo; Refti Handini Listyani (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
Globalization brings changes in various fields, one of which is the transportation sector. Currently, there is a massive change in the transportation system in urban areas such as Surabaya. Modernization of transportation in Surabaya has occurred since 2021 through the policy of providing modern transportation such as Suroboyo Bus and Trans Semanggi. Both transportations have a big impact on the lives of pedicab drivers in Bratang Terminal. This research aims to analyze the form of transportation progress and how the power relations between the government and becak drivers in the context of structural poverty. Using a qualitative approach with observation, interview, and documentation techniques, as well as analysis of Michel Foucault's power relations theory, this study found that non-inclusive transportation policies have created a new form of domination that marginalizes informal worker groups, in this case becak drivers. The modernization has caused them to experience a significant decrease in income, loss of participation space, and increased socio-economic vulnerability of pedicab drivers. These findings suggest that efficiency-based policies without considering social sustainability can exacerbate inequality. Therefore, transportation policies that are not only environmentally friendly and efficient, but also socially just and participatory are needed to ensure that no group is excluded from the urban development process.